2007
DOI: 10.1016/j.taap.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Low level arsenic promotes progressive inflammatory angiogenesis and liver blood vessel remodeling in mice

Abstract: The vascular effects of arsenic in drinking water are global health concerns contributing to human disease worldwide. Arsenic targets the endothelial cells lining blood vessels and endothelial cell activation or dysfunction may underlie the pathogenesis of both arsenic-induced vascular diseases and arsenic-enhanced tumorigenesis. The purpose of the current studies was to demonstrate that exposing mice to drinking water containing environmentally relevant levels of arsenic promoted endothelial cell dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 57 publications
(116 reference statements)
3
41
0
Order By: Relevance
“…Capillarization was confirmed in confocal images of sections stained with anti-PECAM-1, demonstrating a reciprocal dose-response relationship for arsenic-stimulated junctional PECAM-1 expression relative to porosity ( Figure 2A). As in previous studies (22,23), there were no signs of SEC injury or cell death, nor were there any signs of injury in surrounding stellate cells or hepatocytes.…”
Section: Arsenic Stimulated Dose-dependent Capillarization and Pecam-supporting
confidence: 82%
See 4 more Smart Citations
“…Capillarization was confirmed in confocal images of sections stained with anti-PECAM-1, demonstrating a reciprocal dose-response relationship for arsenic-stimulated junctional PECAM-1 expression relative to porosity ( Figure 2A). As in previous studies (22,23), there were no signs of SEC injury or cell death, nor were there any signs of injury in surrounding stellate cells or hepatocytes.…”
Section: Arsenic Stimulated Dose-dependent Capillarization and Pecam-supporting
confidence: 82%
“…Decreased liver metabolism of lipids, glucose, and other nutrients promotes atherogenesis after capillarization in response to several environmental stressors and aging (13,18). We previously demonstrated that arsenic stimulates SEC capillarization and remodeling of the liver vasculature (22,23). Our present results provide support for an arsenic-stimulated mechanism that requires Nox2-based oxidase-generated oxidants to defenestrate and capilliarize SECs as well as impair their physiological functions.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations